Associations between plasma total homocysteine, blood pressure stages and pulse wave velocity in Chinese rural community population. (2nd November 2015) - Qian, Geng; Zeng, Long-Huan; Liu, Yu-Qi; Cao, Feng; Chen, Yun-Dai; Zheng, Mei-Li; Yang, Xin-Chun; Xu, Xi-Ping; Huo, Yong
Abstract : The aim of the study was to examine the associations among plasma total homocysteine (tHcy) and blood pressure (BP) stages and brachial–ankle pulse wave velocity (ba-PWV) in a Chinese rural community population. In this cross-sectional study, 2148 rural community subjects with normotension and mild hypertension (HTN) were classified into four groups according to ba-PWV level. Multivariate regression showed that ba-PWV was significantly and independently correlated with tHcy (β = 5.32, p < 0.001) in the entire study population. Moreover, ba-PWV showed a significant increase with increasing plasma tHcy level in subjects with both high normal BP and grade 1 HTN ( p < 0.05). Compared with optimal BP stage, ba-PWV was significantly associated with high normal BP stage (β = 193, p < 0.001) and grade 1 HTN (β = 413, p < 0.001).There was a statistical interaction effect between high normal BP stage and optimal BP stage ( p = 0.045). The similar result was found between subjects with optimal BP and those with grade 1 HTN ( p = 0.037). In conclusion, tHcy was independently correlated with ba-PWV in subjects with high normal BP and grade 1 HTN. High normal BP and grade 1 HTN may worsen the impact of tHcy on arterial stiffness in a Chinese rural community population.